Completeness of Intervention Reporting of Clinical Trials Published in Highly Ranked Obesity Journals. Issue 2 (19th December 2020) - Rauh, Shelby Lynn; Turner, D'Arcy; Jellison, Sam; Allison, David B.; Fugate, Colony; Foote, Greyson; Vassar, Matt
Abstract : Objective: Randomized controlled trials (RCTs) play a crucial role in the research and advancement of medical treatment. A cross‐sectional study design was utilized to analyze the completeness of intervention reporting using the Template for Intervention Description and Replication (TIDieR) checklist and to evaluate factors associated with intervention reporting. A comparison of the completeness of intervention reporting before and after the publication of TIDieR was sought. Methods: PubMed was searched for RCTs in the top 10 obesity journals per the Google h5‐index. After excluding non‐RCTs, 300 articles were randomly sampled. After assessing each publication for eligibility, two authors (SLR and DT) extracted data related to intervention reporting from records in an independent, masked fashion. Data were then verified and analyzed. Results: The analysis revealed that the quality of intervention reporting is quite variable. Overall, no statistically significant difference in the quality of intervention reporting before and after the release of TIDieR guidelines was found. In general, obesity research has good intervention reporting in areas such as the mode of delivery, material lists for intervention, and procedure lists. However, four main areas in which obesity researchers can improve reporting quality were determined. These include providing the expertise and background of intervention providers and providing statements regarding the assessment of fidelity of the intervention. Conclusions: Urgent intervention is warranted to improve the quality of research reporting in obesity research, which is a fundamental component of obesity management. This will likely require a unified approach from researchers, journals, and funding sources.